2019
DOI: 10.1088/1755-1315/391/1/012024
|View full text |Cite
|
Sign up to set email alerts
|

Biology and population dynamics analysis of fringescale sardine (Sardinella fimbriata) in Bali Strait waters, Indonesia

Abstract: Fringescale sardine (Sardinella fimbriata) is small pelagic fish that has an increasing production every year. This can trigger the occurrence of overfishing, so it is necessary to study the biology and dynamic population of fish. This research was conducted in December 2016 -May 2017. The purpose of this research was to determine the biological aspects and population dynamic of fringescale sardine (S. fimbriata) in Bali Strait. Samples were obtained from surface gillnet landed in Muncar fishing port, with 147… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…Compared to previous studies, similar results were obtained from Banda Aceh with negative allometric growth (b < 3), which was 2.44 (Perdana et al, 2018). Bintoro et al (2019) also reported a negative allometric growth (b = 2.804), whereas research on the southeastern coast of India, the Bay of Bengal and the East Indian Ocean showed 3.14 (b > 3) (Karuppiah et al, 2020). The differences in the b values were due to differences in environmental conditions and the caught fish size.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Compared to previous studies, similar results were obtained from Banda Aceh with negative allometric growth (b < 3), which was 2.44 (Perdana et al, 2018). Bintoro et al (2019) also reported a negative allometric growth (b = 2.804), whereas research on the southeastern coast of India, the Bay of Bengal and the East Indian Ocean showed 3.14 (b > 3) (Karuppiah et al, 2020). The differences in the b values were due to differences in environmental conditions and the caught fish size.…”
Section: Discussionmentioning
confidence: 94%
“…After that, it continued with the determination of the cohort of long-frequency distribution data using the Batthacharya method (Sparre andVenema, 1998 in Tangke et al, 2021). Analysis of the long-weight relationship was done using the Pauly equation (Bintoro et al, 2019;Bintoro et al, 2020) with the equation W = aLb, where W is the body weight of the fish, L is the total length, a is the intercept and b is the slope. This equation is then converted into a linear equation to obtain the values of a and b, namely Log W = Log a + b Log L. Estimated parameters a and b are obtained using regression analysis with Log W as Y and Log L as x with the equation y=a+bx.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bintoro (2019) stated that the length of the first mature gonad fringescale sardinella in the Bali Strait for males and females was 11,95 cm and 10,79 cm respectively [6]. In the study of Aryuningka (2016) in the Sunda Strait, the first mature female fringescale sardinella gonad is 157 mm.…”
Section: Ningrum Et Al (2015) Stated That By Comparingmentioning
confidence: 98%
“…After analyzing all the obtained data, if the length of fish that is caught most (Lc) less than LM, it can be concluded that the fishing gear is not selective and vice versa, but this remains based on each species. To obtain data for LM the main target catch by referring to the previous research such as research of Bintoro [6] for fringescale sardinella, Nugraha [7] for spotted sardinella, and Fauziyah (2012) for devs' anchovy.…”
Section: The Proportion Of Fish Eligible Catching Biologicallymentioning
confidence: 99%